METODE FLOOR TIME TERHADAP PENAMBAHAN KOSAKATA ANAK AUTIS DI SLB - AJENG PRADINI, NIKE (Jurnal Pendidikan Khusus, 2015)
ABSTRACT Language skills are important aspect in child development. To improve child language is through addition of vocabulary. Learning method applied in additional child vocabulary in this research is floor time metode. The method of floor time is a way to build interaction based on child interest for connecting emotion, behaviour and language without any force, a child has an active role in language development.  The purpose of the research is prove an influence in floor time method to addition of  vocabulary for children with disability in SLB (School Special Ecuation) PurnaYuda Bhakti Surabaya. The research method is quantitative approach and research design “the one group, pre test – post test design”, the data was collected by using partipants's observation and documentation. The observation is applied to gain additional vocabulary of child with autism prior to treatment and afterwards. Meanwhile, the documentation data is to be made as supporting data or evidence that the research has been performed. The research result shows that before floor time method has been gived, the obtained average is 45 and after that the obtained average 73. This shows that there is a significant increase. Value Zh = 2,05 higher than crisis value 5% Zt=+1,96 which means that Ho is rejected an Ha is accepted. Therefore, it is concluded that there is an influence of floor time method to addition of vocabulary for child with autism in SLB (School for Special Education) purnayuda bhakti Surabaya.   Keyword: floor time method, addition of vocabulary